Word-Initial Prevocalic [h-] in Middle English - Wełna, Jerzy (Studia Anglica Posnaniensia, 2021)
The present contribution discusses the phonological reality of initial fricative h- in words of Germanic and French origin in dialectally identified 106 texts from the Innsbruck Corpus of Middle English Prose (Markus 2008), with the focus on native words where initial h- is frequently mute, as confirmed by (a) h-less spellings like ouse for house or especially (b) the use of the article an before h-nouns. In the early texts a phrase like an house may testify to the survival of the historical determiner (OE ān) put before both initial vowels and consonants, but in later texts this position may indicate mute initial h- in the following noun (or in an adjective before a noun). The paper offers numerical data concerning such distributions in particular Corpus texts as well as analogous data referring to the adjectives MIN and THIN (later on my and thy), where the final nasal consonant was lost when used in the function of an attribute. Consequently, this development led to the rise of a set of possessive adjectives with a syntactic, not phonological, distribution The data from the Innsbruck Corpus seem to indicate that an early loss of initial prevocalic h- in Middle English words of Germanic origin took place in particular texts rather than in texts from the whole region. The evidence from the Corpus shows that the implementation of the contemporary distribution, i.e., a before consonants and an before vowels, had a partly regional character, its first traces coming from as early as the 13th century.